2006
DOI: 10.1111/j.1468-2982.2006.01210.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Frequent Headache in the General Population: Prevalence and Associated Factors

Abstract: We studied the nature and extent of comorbidity of chronic frequent headache (CFH) in the general population and the influence of CFH and comorbidity on quality of life. Subjects with CFH (headache on >14 days/month) were identified in a general health survey. We sent a second questionnaire including questions on comorbidity and quality of life to subjects with CFH and subjects with infrequent headache (IH) (1-4 days/month). We recoded comorbidity by using the Cumulative Illness Rating Scale (CIRS) and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
106
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 22 publications
(34 reference statements)
7
106
1
7
Order By: Relevance
“…Generally, research supports the former hypothesis (e.g., Wiendels et al, 2006;Hagen et al, 2002), and we agree in the context of the SSS-pain relationship. However, a longitudinal design is required to draw firm conclusions, and we hope Wave 2 will enable this.…”
Section: Sss Measuresupporting
confidence: 58%
“…Generally, research supports the former hypothesis (e.g., Wiendels et al, 2006;Hagen et al, 2002), and we agree in the context of the SSS-pain relationship. However, a longitudinal design is required to draw firm conclusions, and we hope Wave 2 will enable this.…”
Section: Sss Measuresupporting
confidence: 58%
“…Data were analysed using non-parametric tests for categorical variables, and with t-tests for continuous data where differences were compared between diagnostic groups. Statistical methods are described in details elsewhere [18].…”
Section: Discussionmentioning
confidence: 99%
“…In another family practice study, Weindels et al found that compared to patients with less frequent headache episodes, a group with frequent headaches (≥ 15 days per month) were significantly more likely to have somatic problems, like gastroenterological and musculoskeletal disorders [18], as well as more psychiatric disorders and medication over-use [19]. Both frequent headache and comorbidity were associated with lower quality of life [19].…”
Section: Relationship To Other Studiesmentioning
confidence: 99%
“…10,15 Observational and population-based studies describe progressive migraine headaches that become CDHs, a condition that affects 3% to 5% of the population with episodic headaches. [16][17][18][19][20][21] Chronic daily headaches are defined as primary headaches that occur at least 15 days per month, 22-26 although they are not described in the International Classification of Headache Disorders (ICHD)-2 criteria.…”
Section: Discussionmentioning
confidence: 99%
“…26 Most notably, the headache worsens during the period of medication overuse. 18,19,21,23 What differentiates the quality of MOHs from CTTHs most clearly is that MOHs worsen significantly with mental or physical exertion, whereas CTTHs do not. Medication overuse headaches occur in approximately 1% of the population 28 and can be a major contributing factor in the transformation of episodic headaches to CDHs.…”
Section: Discussionmentioning
confidence: 99%